Education aspirations and barriers to achievement for young people in Ethiopia - Tafere, Y (Young Lives, 2014)
This paper reports on the educational aspirations and the challenges facing children living in poor communities in Ethiopia. Using Young Lives survey and qualitative longitudinal data, the paper finds that children hold high educational aspirations and make much effort to achieve their ambitions. Children in higher grades at school maintained their high aspirations. Children have demonstrated their agency in their capacity to aspire high and work hard to attain their ambitions. The results also suggest that poverty has an impact on potential achievements. Despite making every effort to attain their aspirations, some children have failed to do so, or have modified their stated desires. The findings contest at least two widely held assumptions. First, that poor people have low levels of aspiration and do not make any effort because they believe in ‘fate’ rather than hard work, and therefore policies should aim to ‘raise’ their aspirations. Second, poor children, mainly in Africa, have ‘unrealistic’ aspirations, thus, they should be ‘reoriented’. The paper argues that interventions should not be on the ‘raising’ or ‘reorientation’ of aspirations, but on helping young people to achieve what they have aspired to. The ‘raising’ of aspirations is less relevant for young people motivated by the fast expansion of schooling in their country and spurred on by poverty, who do not lack aspirations. ‘Reorientation’ hinders children’s capacity for aspirations and achievements, and is thus detrimental to the national effort for poverty reduction, which could be enhanced by people with high levels of education. Addressing the structural impediments to achievement would be more helpful because achievements inspire the generation to come.